Analisis Pengelolaan Media Humas Digital pada Media Sosial Instagram @riliv - Anisa Diniati; Evi Cristiana; Moch Armien Syifaa Sutarjo; Sri Dewi Setiawati (MediaTor (Jurnal Komunikasi), 2022)
Social media is essential in building relationships between companies and their audiences. Not only playing a role in creating content and disseminating information, but the company's social media management team also needs to develop a strategic plan that is consistent and sustainable. This study examines how the Riliv Social Media Strategist team manages Instagram @riliv social media. This research focuses on the activities carried out in digital media, the characteristics of the use of digital media to represent the company in terms of the use of writing style, to strategies structured in such a way as building public trust and awareness of followers. The method used is a quantitative approach with a descriptive type of research. The results showed that the social media management efforts carried out by the Reliv Social Media Strategist team were structured and scheduled, starting from upload mapping, collaboration, creating content ideas, and activity evaluation. The forms of uploaded content are also very diverse with valid and consistent information on Riliv's philosophy as a psychology service start-up. Almost all the features on the Instagram application are used to build good relationships and closeness with their followers, especially the comment feature and direct message feature as interactive media that are more private.